Hubungan masyarakat pada transaksi jual-beli warung makan sederhana - Nurjihan, Mumtazah (Maliki Interdisciplinary Journal, 2023)
Social interaction is a relationship between humans that is often found in social life. Activities that often involve social interaction are also often found in places where buying and selling transactions are carried out, one of which is in food stalls. In this article the author will discuss types of social interaction or what is also called community relations in the practice of buying and selling transactions at simple food stalls. This article also discusses tips for starting and running a low-end culinary business to minimize failure.